Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Addressing Bias in Non‐Probability Fisheries Surveys Using Multilevel Regression and Poststratification Approaches - Zachary Radford; Wendy Edwards; Samantha Hook; Bridgid Bell; Rebecca Mills; Grace Farrell; Martin J. Genner; Stephen D. Simpson; Kieran Hyder (Fish and Fisheries, 2026)
Quantifying harvest of fish stocks is challenging as census data are often unavailable, so surveys are required. Traditional probability‐based surveys use random sampling to obtain representative data that can be scaled to estimate total impact. However, these surveys are costly, so cheaper, non‐probability, citizen science surveys of self‐selected participants are becoming commonplace. Respondents in these surveys may not be representative and inclusion probabilities are unknown, making weighting difficult. This resembles exit polls, which successfully predict election outcomes using Multi‐level Regression and Post‐stratification (MRP), but this has not been tested in fisheries. This study applied MRP to quantify UK recreational sea angling (RSA) participation and catches using data from the UK Sea Angling Diary Project. This represents a ‘worst‐case’ scenario, as there is no sampling frame and no mandatory reporting. Five Bayesian multi‐level models were fitted to two survey datasets: one quantifying participation and days fished, and another location, numbers, and weight of fish caught. Predictions were post‐stratified using UK census data. Estimates from the traditional reweighting and MRP were compared, and a simulation approach was used to assess the accuracy and precision of the two methods. MRP reduced self‐selection bias and improved estimates in under‐represented groups, producing a 40% and 61% improvement for participation and catch, respectively. Average annual UK RSA participation was estimated to be 688,000 anglers, with 6.1 million days fished. Annual catch estimates were 32.4 million fish, weighing 14,876 t. This study demonstrates the value of MRP for reducing bias when analysing and scaling non‐probabilistically collected survey data.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Evaluation of organic products to control blueberry rust - Kara M. Barry; Michele Buntain; Eugene Chau; Melinda Simpson; Stephen Morris; Jay Anderson (Crop Protection, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Scope effects and willingness to pay for deep sea management practices within and beyond national jurisdictions - Bui Bich Xuan; Claire W. Armstrong; Stephen Hynes; Isaac Ankamah-Yeboah; Katherine Simpson; Godwin K. Vondolia (Journal of Environmental Management, 2025)

CSF Markers of TG6 Autoimmunity in Gluten Ataxia - Mara-Luciana Floare; Stephen B. Wharton; Julie E. Simpson; Daniel Aeschlimann; Marios Hadjivassiliou (The Cerebellum, 2025)
Gluten ataxia (GA) is the primary neurological manifestation of gluten sensitivity, characterised by loss of Purkinje cells throughout the cerebellar cortex and rooted in autoimmunity to transglutaminase 6 (TG6). Previous studies have shown the contribution of serum anti-TG6 antibodies to disease progression; however, it remains unclear where these antibodies are produced and how they gain access into the brain parenchyma. This study aims to provide an immunological assessment of the CSF in patients with GA to better define the humoral response contributing to disease pathophysiology. In this observational study we assessed the presence of plasma cells in the CSF of 20 patients with GA and 6 controls. CSF from 16 of the GA patients and from all 6 controls was investigated for the presence of anti-TG6 IgA antibodies. Immunohistochemistry for CD138 was performed to assess the presence of plasma cells in the cerebellum and spinal cord of 4 cases with GA, 4 ataxia controls and 4 neurologically healthy controls. A significant increase in anti-TG6 IgA antibodies was detected in the CSF of patients with GA compared to controls, with no correlation between CSF and serum levels of anti-TG6 IgA antibodies for either experimental group. CD138 + cells were present in the CSF of 2 patients with GA and in the cerebellum and spinal cord of 3 post-mortem cases of GA. In a subpopulation of patients with GA intrathecal presence of plasma cells and TG6 antibodies is a feature of the disease, likely associated with prolonged disease duration and continuous exposure to gluten.

A highly prevalent and specific cryptic plasmid pBI143 for human fecal pollution tracking in a subtropical urban river - Yawen Liu; Wendy J.M. Smith; Metasebia Gebrewold; Rory Verhagen; Stephen Cook; Stuart L. Simpson; Bethany Oceguera Johnson; Kyle Bibby; Warish Ahmed (Water Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Lionfish (Pterois volitans) do not show directional preferences for ambient underwater soundscapes during diurnal hours - Roxanne B Holmes; Nadia M. Hamilton; Stephen D. Simpson; James E. Herbert-Read (Marine Biology, 2025)
Sound is a valuable cue in the marine environment that can inform animals about habitat location and community composition. Indeed, sound is often used for orientation and navigation by larval reef fishes during settlement. However, despite sound’s role in the early life of reef fishes, whether post-settlement reef fishes use ambient soundscapes to inform their movement decisions remains less clear. In an in-situ playback experiment in Curaçao, the Dutch Caribbean, settled individuals of an invasive predator, the Indo-Pacific lionfish ( Pterois volitans ), showed no preference to move towards the playbacks of two different habitat types during daylight hours. In particular, lionfish did not prefer to move towards the sounds of sandy or reef habitat playbacks when tested against a silent control. Moreover, when given a choice between simultaneous sandy and reef habitat playbacks, lionfish showed no preference for the soundscape of either habitat type. While the activity of lionfish was strongly correlated with their body size, with larger fish being more active, activity was not affected by habitat playback, nor did body size affect their preference for the soundscapes of either habitat type. While acoustic lures have been speculated to be a promising addition to existing lionfish trap designs, daytime playbacks of ambient soundscapes are unlikely to be successful in attracting lionfish post-settlement, ultimately affecting their efficacy.

Eating disorder risk among Australian youth starting a diet in the community - Melissa J. Pehlivan; Mirei Okada; Jane Miskovic-Wheatley; Sarah Barakat; Stephen Touyz; Stephen J. Simpson; Kristi Griffiths; Andrew Holmes; Sarah Maguire (Appetite, 2024)

Artificial Light Increases Nighttime Prevalence of Predatory Fishes, Altering Community Composition on Coral Reefs - Emma Weschke; Jules Schligler; Isla Hely; Thibaut Roost; Jo‐Ann Schies; Ben Williams; Bartosz Dworzanski; Suzanne C. Mills; Ricardo Beldade; Stephen D. Simpson; Andrew N. Radford (Global Change Biology, 2024)
Artificial light at night (ALAN) is an anthropogenic pollutant that is intensifying and expanding in marine environments, but experimental studies of community‐level effects are generally lacking. The inshore, shallow, and clear‐water locations of coral reefs and their diverse photosensitive inhabitants make these ecosystems highly susceptible to biological disturbances; at the same time, their biodiversity and accessibility make them model systems for wider insight. Here, we experimentally manipulated ALAN using underwater LED lights on a Polynesian reef system to investigate the influence on localised nighttime fish communities compared to control sites without ALAN. We collected infrared video censuses of baseline communities prior to manipulation, which we repeated following short‐term (mean of three nights) and prolonged (mean of 25 nights) exposures to ALAN. Short‐term ALAN exposure did not induce any significant alterations to the nighttime fish community, but prolonged ALAN exposure increased nighttime species richness. Species compositions exposed to prolonged ALAN were more dissimilar from their baseline compared to control sites. The difference between community compositions at prolonged ALAN exposure and control sites was not apparent at the family level; instead, it was observed from the composition of trait guilds. Following prolonged ALAN exposure, more diurnal and nocturnal predatory species (piscivores, invertivores, and planktivores)—particularly those that are site‐attached or mobile within reefs—were present in nighttime assemblages. Our experimental findings show that coastal ALAN could cause trophic imbalances and circadian disturbances in localised nighttime reef fish communities. Given that community‐wide consequences were only apparent after prolonged ALAN exposure suggests that management of the duration of artificial lighting could potentially be used to reduce impacts on marine ecosystems.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Description and taxonomic assessment of fossil Cercopithecidae from the Pliocene Galili Formation (Ethiopia) - Hailay G. Reda; Stephen R. Frost; Evan A. Simons; Jay Quade; Scott W. Simpson (Journal of Human Evolution, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Pseudomonas umsongensis GO16 as a platform for the in vivo synthesis of short and medium chain length polyhydroxyalkanoate blends - Federico Cerrone; Binbin Zhou; Agathe Mouren; Luc Avérous; Stephen Conroy; Jeremy C. Simpson; Kevin E. O'Connor; Tanja Narancic (Bioresource Technology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Transcriptomic Profiling Reveals Discrete Poststroke Dementia Neuronal and Gliovascular Signatures - Rachel Waller; Yoshiki Hase; Julie E. Simpson; Paul R. Heath; Matthew Wyles; Rajesh N. Kalaria; Stephen B. Wharton (Translational Stroke Research, 2023)
Poststroke dementia (PSD) is associated with pathology in frontal brain regions, in particular dorsolateral prefrontal cortex (DLPFC) neurons and white matter, remote from the infarct. We hypothesised that PSD results from progressive DLPFC neuronal damage, associated with frontal white matter gliovascular unit (GVU) alterations. We investigated the transcriptomic profile of the neurons and white matter GVU cells previously implicated in pathology. Laser-capture microdissected neurons, astrocytes and endothelial cells were obtained from the Cognitive Function After Stroke cohort of control, PSD and poststroke non-dementia (PSND) human subjects. Gene expression was assessed using microarrays and pathway analysis to compare changes in PSD with controls and PSND. Neuronal findings were validated using NanoString technology and compared with those in the bilateral common carotid artery stenosis (BCAS) mouse model. Comparing changes in PSD compared to controls with changes in PSND compared to controls identified transcriptomic changes associated specifically with dementia. DLPFC neurons showed defects in energy production (tricarboxylic acid (TCA) cycle, adenosine triphosphate (ATP) binding and mitochondria), signalling and communication (MAPK signalling, Toll-like receptor signalling, endocytosis). Similar changes were identified in neurons isolated from BCAS mice. Neuronal findings accompanied by altered astrocyte communication and endothelium immune changes in the frontal white matter, suggesting GVU dysfunction. We propose a pathogenic model in PSD whereby neuronal changes are associated with frontal white matter GVU dysfunction leading to astrocyte failure in supporting neuronal circuits resulting in delayed cognitive decline associated with PSD. Therefore, targeting these processes could potentially ameliorate the dementia seen in PSD.

The role of acoustics within the sensory landscape of coral larval settlement - Josh W. Pysanczyn; Elizabeth A. Williams; Emelie Brodrick; Daniel Robert; Jamie Craggs; Kristen L. Marhaver; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recruitment of coral larvae on reefs is crucial for individual survival and ecosystem integrity alike. Coral larvae can detect and respond to a wide range of biotic and abiotic cues, including acoustic cues, to locate suitable sites for settlement and metamorphosis. However, the acoustic ecology of coral larvae, including how they perceive auditory cues, remains poorly understood. In this mini-review we consider both ex situ physiology and behavior, and in situ ecological and behavioral studies, to first provide an updated overview of the abiotic and biotic cues used by coral larvae to guide settlement. We then explore in detail the use of acoustic cues and the current literature on behavioral responses to acoustic stimuli. Finally, we discuss gaps in our understanding of the mechanisms by which coral larvae detect acoustic cues, highlighting a novel application of technology to explore these sensory capabilities. We also address how larval phonotaxis, i.e., the ability to orient to a sound cue, can be applied to coral reef conservation. Current research suggests that acoustic cues are likely used at small spatial scales, and that coral larvae may have directional acoustic sensitivity enabling phonotactic behavior. Recruitment of coral larvae on reefs is significantly influenced by habitat-specific soundscape variation and likely affected by anthropogenic disturbance. We propose a novel application of the remote sensing technology, micro-scanning laser Doppler vibrometry (LDV), to quantify the micromechanical responses of putative acoustically sensitive epidermal microstructures. We then highlight the potential for incorporation of acoustic enrichment techniques in coral reef conservation and restoration interventions.

Sea temperature is the primary driver of recent and predicted fish community structure across Northeast Atlantic shelf seas - Louise A. Rutterford; Stephen D. Simpson; Bjarte Bogstad; Jennifer A. Devine; Martin J. Genner (Global Change Biology, 2023)
Climate change has strongly influenced the distribution and abundance of marine fish species, leading to concern about effects of future climate on commercially harvested stocks. Understanding the key drivers of large‐scale spatial variation across present‐day marine assemblages enables predictions of future change. Here we present a unique analysis of standardised abundance data for 198 marine fish species from across the Northeast Atlantic collected by 23 surveys and 31,502 sampling events between 2005 and 2018. Our analyses of the spatially comprehensive standardised data identified temperature as the key driver of fish community structure across the region, followed by salinity and depth. We employed these key environmental variables to model how climate change will affect both the distributions of individual species and local community structure for the years 2050 and 2100 under multiple emissions scenarios. Our results consistently indicate that projected climate change will lead to shifts in species communities across the entire region. Overall, the greatest community‐level changes are predicted at locations with greater warming, with the most pronounced effects at higher latitudes. Based on these results, we suggest that future climate‐driven warming will lead to widespread changes in opportunities for commercial fisheries across the region.

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

Marine invertebrates and noise - Marta Solé; Kenzo Kaifu; T. Aran Mooney; Sophie L. Nedelec; Frédéric Olivier; Andrew N. Radford; Mirella Vazzana; Matthew A. Wale; Jayson M. Semmens; Stephen D. Simpson; Giuseppa Buscaino; Anthony Hawkins; et al. (Frontiers in Marine Science, 2023)
Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs. Recent studies have revealed that a wide diversity of invertebrates are also sensitive to sounds, especially via sensory organs whose original function is to allow maintaining equilibrium in the water column and to sense gravity. Marine invertebrates not only represent the largest proportion of marine biomass and are indicators of ocean health but many species also have important socio-economic values. This review presents the current scientific knowledge on invertebrate bioacoustics (sound production, reception, sensitivity), as well as on how marine invertebrates are affected by anthropogenic noises. It also critically revisits the literature to identify gaps that will frame future research investigating the tolerance to noise of marine ecosystems.

Occurrence of multiple respiratory viruses in wastewater in Queensland, Australia: Potential for community disease surveillance - Warish Ahmed; Aaron Bivins; Mikayla Stephens; Suzanne Metcalfe; Wendy J.M. Smith; Kwanrawee Sirikanchana; Masaaki Kitajima; Stuart L. Simpson (Science of The Total Environment, 2023)

Examining current best-practices for the use of wild post-larvae capture, culture, and release for fisheries enhancement - Laura E. Richardson; Philippe Lenfant; Leo J. Clarke; Amelie Fontcuberta; Anaïs Gudefin; Gilles Lecaillon; Lewis Le Vay; Andrew N. Radford; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Demand for marine fisheries is rising despite global impacts on the productive capacity of wild fish stocks due to overfishing, habitat loss, and global warming. Fisheries enhancement programs—aimed at augmenting stocks by releasing juveniles into the wild—are expected to play an increasingly important auxiliary role in addressing capture-based fishery limitations into the future. However, concerns exist over the impacts and efficacy of aquaculture-based enhancement (ABE), releasing captive-bred fish into wild populations. An alternative but understudied approach for fisheries enhancement is wild post-larvae capture, culture, and release (PCCR). Here, we provide an overview of the PCCR process, from initial planning to measuring success, providing an overview of its implementation in a viable finfish fishery, the white seabream Diplodus sargus in the Mediterranean. We discuss management application of PCCR-based enhancement and its limitations, highlighting existing knowledge gaps and future research required to realize the full potential of this alternative approach. Notwithstanding some limitations–including limited uptake for full evaluation, some species restrictions, density-dependent mortality, and the remaining open challenge for stock enhancement generally of tracking released fish through to reproduction–PCCR offers potential as a credible auxiliary management tool for fisheries restoration.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Commissioning measurements on an Elekta Unity MR-Linac - Marcus Powers; John Baines; Robert Crane; Chantelle Fisher; Stephen Gibson; Linda Marsh; Bronwyn Oar; Ariadne Shoobridge; Emily Simpson-Page; Marchant Van der Walt; Glenn de Vine (Physical and Engineering Sciences in Medicine, 2022)
Magnetic resonance-guided radiotherapy technology is relatively new and commissioning publications, quality assurance (QA) protocols and commercial products are limited. This work provides guidance for implementation measurements that may be performed on the Elekta Unity MR-Linac (Elekta, Stockholm, Sweden). Adaptations of vendor supplied phantoms facilitated determination of gantry angle accuracy and linac isocentre, whereas in-house developed phantoms were used for end-to-end testing and anterior coil attenuation measurements. Third-party devices were used for measuring beam quality, reference dosimetry and during treatment plan commissioning; however, due to several challenges, variations on standard techniques were required. Gantry angle accuracy was within 0.1°, confirmed with pixel intensity profiles, and MV isocentre diameter was < 0.5 mm. Anterior coil attenuation was approximately 0.6%. Beam quality as determined by TPR 20,10 was 0.705 ± 0.001, in agreement with treatment planning system (TPS) calculations, and gamma comparison against the TPS for a 22.0 × 22.0 cm 2 field was above 95.0% (2.0%, 2.0 mm). Machine output was 1.000 ± 0.002 Gy per 100 MU, depth 5.0 cm. During treatment plan commissioning, sub-standard results indicated issues with machine behaviour. Once rectified, gamma comparisons were above 95.0% (2.0%, 2.0 mm). Centres which may not have access to specialized equipment can use in-house developed phantoms, or adapt those supplied by the vendor, to perform commissioning work and confirm operation of the MRL within published tolerances. The plan QA techniques used in this work can highlight issues with machine behaviour when appropriate gamma criteria are set.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

3D printed brachytherapy jig for Reference Air Kerma Rate calibration - Emily Simpson-Page; Lynsey Hamlett; Dominika Lew; Holly Stephens; Rachael Wilks; Tanya Kairn; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Development of fly tolerance to consuming a high-protein diet requires physiological, metabolic and transcriptional changes - Ihor S. Yurkevych; Lindsey J. Gray; Dmytro V. Gospodaryov; Nadia I. Burdylyuk; Kenneth B. Storey; Stephen J. Simpson; Oleh Lushchak (Biogerontology, 2020)

Bayesian Inverse Transient Analysis for Pipeline Condition Assessment: Parameter Estimation and Uncertainty Quantification - Chi Zhang; Martin F. Lambert; Jinzhe Gong; Aaron C. Zecchin; Angus R. Simpson; Mark L. Stephens (Water Resources Management, 2020)

Can we project changes in fish abundance and distribution in response to climate? - Jose A. Fernandes; Louise Rutterford; Stephen D. Simpson; Momme Butenschön; Thomas L. Frölicher; Andrew Yool; William W. L. Cheung; Alastair Grant (Global Change Biology, 2020)
Large‐scale and long‐term changes in fish abundance and distribution in response to climate change have been simulated using both statistical and process‐based models. However, national and regional fisheries management requires also shorter term projections on smaller spatial scales, and these need to be validated against fisheries data. A 26‐year time series of fish surveys with high spatial resolution in the North‐East Atlantic provides a unique opportunity to assess the ability of models to correctly simulate the changes in fish distribution and abundance that occurred in response to climate variability and change. We use a dynamic bioclimate envelope model forced by physical–biogeochemical output from eight ocean models to simulate changes in fish abundance and distribution at scales down to a spatial resolution of 0.5°. When comparing with these simulations with annual fish survey data, we found the largest differences at the 0.5° scale. Differences between fishery model runs driven by different biogeochemical models decrease dramatically when results are aggregated to larger scales (e.g. the whole North Sea), to total catches rather than individual species or when the ensemble mean instead of individual simulations are used. Recent improvements in the fidelity of biogeochemical models translate into lower error rates in the fisheries simulations. However, predictions based on different biogeochemical models are often more similar to each other than they are to the survey data, except for some pelagic species. We conclude that model results can be used to guide fisheries management at larger spatial scales, but more caution is needed at smaller scales.

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - David O. Obura; Greta Aeby; Natchanon Amornthammarong; Ward Appeltans; Nicholas Bax; Joe Bishop; Russell E. Brainard; Samuel Chan; Pamela Fletcher; Timothy A. C. Gordon; Lew Gramer; Mishal Gudka; et al. (Frontiers in Marine Science, 2019)

Draft genome sequence of the symbiotic Frankia sp. strain BMG5.30 isolated from root nodules of Coriaria myrtifolia in Tunisia - Abdellatif Gueddou; Erik Swanson; Karima Hezbri; Imen Nouioui; Amir Ktari; Stephen Simpson; Krystalynne Morris; W. Kelley Thomas; Faten Ghodhbane-Gtari; Maher Gtari; Louis S. Tisa (Antonie van Leeuwenhoek, 2019)

Physical and chemical impacts of a major storm on a temperate lake: a taste of things to come? - R. Iestyn Woolway; John H. Simpson; David Spiby; Heidrun Feuchtmayr; Ben Powell; Stephen C. Maberly (Climatic Change, 2018)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Diet has independent effects on the pace and shape of aging in Drosophila melanogaster - C. Ruth Archer; Ugofilippo Basellini; John Hunt; Stephen J. Simpson; Kwang Pum Lee; Annette Baudisch (Biogerontology, 2018)

Historical Processes and Contemporary Anthropogenic Activities Influence Genetic Population Dynamics of Nassau Grouper (Epinephelus striatus) within The Bahamas - Krista D. Sherman; R. Andrew King; Craig P. Dahlgren; Stephen D. Simpson; Jamie R. Stevens; Charles R. Tyler (Frontiers in Marine Science, 2017)

Acute oxytocin improves memory and gaze following in male but not female nursery-reared infant macaques - Elizabeth A. Simpson; Annika Paukner; Valentina Sclafani; Stefano S. K. Kaburu; Stephen J. Suomi; Pier F. Ferrari (Psychopharmacology, 2017)

Repeated exposure reduces the response to impulsive noise in European seabass - Andrew N. Radford; Laurie Lèbre; Gilles Lecaillon; Sophie L. Nedelec; Stephen D. Simpson (Global Change Biology, 2016)
Human activities have changed the acoustic environment of many terrestrial and aquatic ecosystems around the globe. Mounting evidence indicates that the resulting anthropogenic noise can impact the behaviour and physiology of at least some species in a range of taxa. However, the majority of experimental studies have considered only immediate responses to single, relatively short‐term noise events. Repeated exposure to noise could lead to a heightened or lessened response. Here, we conduct two long‐term (12 week), laboratory‐based exposure experiments with European seabass ( Dicentrarchus labrax ) to examine how an initial impact of different sound types potentially changes over time. Naïve fish showed elevated ventilation rates, indicating heightened stress, in response to impulsive additional noise (playbacks of recordings of pile‐driving and seismic surveys), but not to a more continuous additional noise source (playbacks of recordings of ship passes). However, fish exposed to playbacks of pile‐driving or seismic noise for 12 weeks no longer responded with an elevated ventilation rate to the same noise type. Fish exposed long‐term to playback of pile‐driving noise also no longer responded to short‐term playback of seismic noise. The lessened response after repeated exposure, likely driven by increased tolerance or a change in hearing threshold, helps explain why fish that experienced 12 weeks of impulsive noise showed no differences in stress, growth or mortality compared to those reared with exposure to ambient‐noise playback. Considering how responses to anthropogenic noise change with repeated exposure is important both when assessing likely fitness consequences and the need for mitigation measures.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Nutritional ecology beyond the individual: a conceptual framework for integrating nutrition and social interactions - Mathieu Lihoreau; Camille Buhl; Michael A. Charleston; Gregory A. Sword; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2015)
Over recent years, modelling approaches from nutritional ecology (known as Nutritional Geometry) have been increasingly used to describe how animals and some other organisms select foods and eat them in appropriate amounts in order to maintain a balanced nutritional state maximising fitness. These nutritional strategies profoundly affect the physiology, behaviour and performance of individuals, which in turn impact their social interactions within groups and societies. Here, we present a conceptual framework to study the role of nutrition as a major ecological factor influencing the development and maintenance of social life. We first illustrate some of the mechanisms by which nutritional differences among individuals mediate social interactions in a broad range of species and ecological contexts. We then explain how studying individual‐ and collective‐level nutrition in a common conceptual framework derived from Nutritional Geometry can bring new fundamental insights into the mechanisms and evolution of social interactions, using a combination of simulation models and manipulative experiments.

Modeling spatiotemporal dynamics of outbreaking species: influence of environment and migration in a locust - Sophie Veran; Stephen J. Simpson; Gregory A. Sword; Edward Deveson; Sylvain Piry; James E. Hines; Karine Berthier (Ecology, 2015)
Many pest species exhibit huge fluctuations in population abundance. Understanding their large‐scale and long‐term dynamics is necessary to develop effective control and management strategies. Occupancy models represent a promising approach to unravel interactions between environmental factors and spatiotemporal dynamics of outbreaking populations. Here, we investigated population dynamics of the Australian plague locust, Chortoicetes terminifera , using density data collected between 1988 and 2010 by the Australian Plague Locust Commission over more than 3 million km 2 in eastern Australia. We applied multistate and autologistic multi‐season occupancy models to test competing hypotheses about environmental and demographic processes affecting the large‐scale dynamics of the Australian plague locust. We found that rainfall and land cover predictors best explained the spatial variability in outbreak probability across eastern Australia. Outbreaks are more likely to occur in temperate than tropical regions, with a faster and more continuous response to rainfall in desert than in agricultural areas. Our results also support the hypothesis that migration tends to propagate outbreaks only locally (over distances lower than 400 km) rather than across climatic regions. Our study suggests that locust outbreak forecasting and management systems could be improved by implementing key environmental factors and migration in hierarchical spatial models. Finally, our modeling framework can be seen as a step towards bridging the gap between mechanistic and more phenomenological models in the spatial analysis of fluctuating populations.

Anthropogenic noise compromises antipredator behaviour in European eels - Stephen D. Simpson; Julia Purser; Andrew N. Radford (Global Change Biology, 2015)
Increases in noise‐generating human activities since the Industrial Revolution have changed the acoustic landscape of many terrestrial and aquatic ecosystems. Anthropogenic noise is now recognized as a major pollutant of international concern, and recent studies have demonstrated impacts on, for instance, hearing thresholds, communication, movement and foraging in a range of species. However, consequences for survival and reproductive success are difficult to ascertain. Using a series of laboratory‐based experiments and an open‐water test with the same methodology, we show that acoustic disturbance can compromise antipredator behaviour – which directly affects survival likelihood – and explore potential underlying mechanisms. Juvenile European eels ( Anguilla anguilla ) exposed to additional noise (playback of recordings of ships passing through harbours), rather than control conditions (playback of recordings from the same harbours without ships), performed less well in two simulated predation paradigms. Eels were 50% less likely and 25% slower to startle to an ‘ambush predator’ and were caught more than twice as quickly by a ‘pursuit predator’. Furthermore, eels experiencing additional noise had diminished spatial performance and elevated ventilation and metabolic rates (indicators of stress) compared with control individuals. Our results suggest that acoustic disturbance could have important physiological and behavioural impacts on animals, compromising life‐or‐death responses.

Dissipation and mixing during the onset of stratification in a temperate lake, W indermere - John H. Simpson; Natasha S. Lucas; Ben Powell; Stephen C. Maberly (Limnology and Oceanography, 2015)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Arthropod food webs become increasingly lipid‐limited at higher trophic levels - Shawn M. Wilder; Michael Norris; Raymond W. Lee; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2013)
Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Erratum to: Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

Cannibalism can drive the evolution of behavioural phase polyphenism in locusts - Vishwesha Guttal; Pawel Romanczuk; Stephen J. Simpson; Gregory A. Sword; Iain D. Couzin (Ecology Letters, 2012)
During outbreaks, locust swarms can contain millions of insects travelling thousands of kilometers while devastating vegetation and crops. Such large‐scale spatial organization is preceded locally by a dramatic density‐dependent phenotypic transition in multiple traits. Behaviourally, low‐density ‘solitarious’ individuals avoid contact with one another; above a critical local density, they undergo a rapid behavioural transition to the ‘gregarious phase’ whereby they exhibit mutual attraction. Although proximate causes of this phase polyphenism have been widely studied, the ultimate driving factors remain unclear. Using an individual‐based evolutionary model, we reveal that cannibalism, a striking feature of locust ecology, could lead to the evolution of density‐dependent behavioural phase‐change in juvenile locusts. We show that this behavioural strategy minimizes risk associated with cannibalistic interactions and may account for the empirically observed persistence of locust groups during outbreaks. Our results provide a parsimonious explanation for the evolution of behavioural plasticity in locusts.

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

A test of the senses: Fish select novel habitats by responding to multiple cues - Chantal M. Huijbers; Ivan Nagelkerken; Pauline A. C. Lössbroek; Ines E. Schulten; Andjin Siegenthaler; Marc W. Holderied; Stephen D. Simpson (Ecology, 2012)
Habitat‐specific cues play an important role in orientation for animals that move through a mosaic of habitats. Environmental cues can be imprinted upon during early life stages to guide later return to adult habitats, yet many species must orient toward suitable habitats without previous experience of the habitat. It is hypothesized that multiple sensory cues may enable animals to differentiate between habitats in a sequential order relevant to the spatial scales over which the different types of information are conveyed, but previous research, especially for marine organisms, has mainly focused on the use of single cues in isolation. In this study, we investigated novel habitat selection through the use of three different sensory modalities (hearing, vision, and olfaction). Our model species, the French grunt, Haemulon flavolineatum , is a mangrove/seagrass‐associated reef fish species that makes several habitat transitions during early life. Using several in situ and ex situ experiments, we tested the response of fish toward auditory, olfactory, and visual cues from four different habitats (seagrass beds, mangroves, rubble, and coral reef). We identified receptivity to multiple sensory cues during the same life phase, and found that different cues induced different reactions toward the same habitat. For example, early‐juvenile fish only responded to sound from coral reefs and to chemical cues from mangroves/seagrass beds, while visual cues of conspecifics overruled olfactory cues from mangrove/seagrass water. Mapping these preferences to the ecology of ontogenetic movements, our results suggest sequential cue use would indeed aid successful orientation to novel key habitats in early life.

Cannibalism in the lifeboat — collective movement in Australian plague locusts - Matthew J. Hansen; Camille Buhl; Sepideh Bazazi; Stephen J. Simpson; Gregory A. Sword (Behavioral Ecology and Sociobiology, 2011)

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

Prey nutrient composition has different effects on Pardosa wolf spiders with dissimilar life histories - Kim Jensen; David Mayntz; Søren Toft; David Raubenheimer; Stephen J. Simpson (Oecologia, 2011)

Group structure in locust migratory bands - Camille Buhl; Gregory A. Sword; Fiona J. Clissold; Stephen J. Simpson (Behavioral Ecology and Sociobiology, 2011)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Dietary ratio of protein to carbohydrate induces plastic responses in the gastrointestinal tract of mice - Allan Sørensen; David Mayntz; Stephen James Simpson; David Raubenheimer (Journal of Comparative Physiology B, 2010)

Gross vs. net income: How plant toughness affects performance of an insect herbivore - Fiona J. Clissold; Gordon D. Sanson; Jenny Read; Stephen J. Simpson (Ecology, 2009)
Leaf biomechanical properties are thought to impose a significant obstacle to herbivores and as such influence patterns of herbivory more than leaf chemistry. However, evidence for the role of structural traits in influencing herbivore food choice and performance has come from correlative studies, whereas the underlying mechanisms have been given little attention. By manipulating the biomechanical properties of a host grass species through a combination of lyophilization and milling, and providing water separately, we were able to compare behavioral, physiological, and developmental responses of the Australian plague locust, Chortoicetes terminifera , to the biomechanical properties of plant food (exemplified by toughness) independently of the food's macronutrient content and the insect's demand for water. Increasing leaf toughness was associated with reduced rates of locust growth and prolonged development, with potential ecological consequences. Poorer performance on the tougher foods was primarily a consequence of a reduced rate of nutrient supply, which occurred as a result of (1) smaller meals being eaten more slowly, (2) slowed gut passage rates, which limited how quickly the next meal could be taken, and (3) reduced efficiency of assimilation of nutrients from food in the gut. In addition, there were deleterious changes in the ratio of protein to carbohydrate assimilated from the gut. Prolonged development time was associated with increased total nutrient demands throughout the extended developmental period. Because these demands could not be met by increased consumption, there was a decreased efficiency of conversion of assimilated nutrients to growth. By disentangling the effects of biomechanical properties from macronutrient and water content we have shown that leaf biomechanical traits can influence chewing herbivores independently of leaf chemical traits.

The Role for Sustainably Managed Forests in Climate Change Mitigation - Steven Ruddell; R. Sampson; Matt Smith; R. Giffen; James Cathcart; John Hagan; Daniel Sosland; John Godbee; John Heissenbuttel; Stephen Lovett; John Helms; William Price; et al. (Journal of Forestry, 2007)
The United States has not ratified the Kyoto Protocol, restricting the ability of forests from participating internationally as greenhouse gas (GHG) emission offset projects. As a result, a proliferation of different registry and program rules is occurring in the United States, providing an opportunity for the US forestry community to mitigate GHG emissions. This article addresses the Kyoto Protocol principles of additionality, permanence, and leakage, and challenges the way that these principles are being used to qualify forest offset projects as climate change mitigation measures. Policy initiatives are proposed for challenging policymakers and the forestry community to rethink sustainably managed forest offset project rules as the United States considers GHG emission reduction legislation.